2011
DOI: 10.4171/em/179
|View full text |Cite
|
Sign up to set email alerts
|

Angle trisection with Origami and related topics

Abstract: Clemens Fuchs received his doctoral degree and his habilitation in mathematics from the Graz University of Technology. Currently he is working as senior researcher and lecturer at ETH Zurich. His main fields of interest are in number theory and diophantine geometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…The recent work of scholars such as Tachi, Demaine, Lang, and Hull strongly contributed to the rise of mathematical studies on origami. Furthermore, it has been demonstrated that origami can be applied to solve mathematical problems such as quadratic, cubic, [40] quartic and quintic equations with rational coefficients, [39] trisect an angle, [40,41] and double the cube. [16,40,42] Therefore, mathematics has been extensively applied for the design and optimization process of origami structures.…”
Section: Background and Terminologymentioning
confidence: 99%
“…The recent work of scholars such as Tachi, Demaine, Lang, and Hull strongly contributed to the rise of mathematical studies on origami. Furthermore, it has been demonstrated that origami can be applied to solve mathematical problems such as quadratic, cubic, [40] quartic and quintic equations with rational coefficients, [39] trisect an angle, [40,41] and double the cube. [16,40,42] Therefore, mathematics has been extensively applied for the design and optimization process of origami structures.…”
Section: Background and Terminologymentioning
confidence: 99%